Representação discursiva sobre a concepção de beleza para mulheres venezuelanas e peruanas residentes no Peru - Robles Muñoz, Mirella Alexandra (2022)
Venezuelan migration in Peru has increased in recent years, with this there has been a controversy, around the judgments issued towards Venezuelan migrants, who are compared to Peruvian women, due to what they physically project. The objective of the article is to analyze the ideological discourses that are built on the representation of beauty towards Venezuelan and Peruvian women in Peru. Methodologically, the reactions, issued by the YouTube website, on videos alluding to Venezuelan and Peruvian women made in Peruvian territory are collected. This research is qualitative and addresses conceptions about the female body, racism and social prejudice. The conclusions indicate that there is a tendency to enhance the negative qualities of Venezuelan migrant women around, above all, cosmetic surgeries; with respect to Peruvian women, there is a tendency to enhance their attributes related to optional qualities such as working and studying.